The use of primary chondrocytes in combination with polycistronic sox-trio plasmid and tert gene transfer for articular cartilage tissue engineering and its bioethical implications - Aisyah Hanani Md Ali@Tahir
A polycistronic SOX-trio plasmid vector was designed using VectorBuilder free software. The combination of SOX5, SOX6 and SOX9 genes resulted in a plasmid vector of more than ten (10) kbp. It is challenging to transfect primary cells culture with a larger than two (2) kbp DNA fragment. Thus, the SOX-trio plasmid DNA’s transfection efficiency was optimised using a lipofection method. The three experimental groups that resulted from the SOX-trio and TERT genes transfected in the chondrocytes were SOX-trio/TERT (SXT), SOX-trio (SX) and TERT. They were observed using fluorescent microscopy. The non-transfected chondrocytes served as a control group. Various histology staining procedures were used to evaluate the presence of cartilaginous pericellular and extracellular matrix (ECM). The matrices production level was evaluated further using sulphated glycosaminoglycan (sGAG) assay for confirmation. The formation of neocartilage or the in vitro 3D “cell-scaffold” tissue constructs was done using chondrocytes seeded in the PLGA-based scaffolds. This step resulted in three ‘cell-scaffold’ experimental groups, namely PLGA/Fibrin/Atelocollagen (PAF), PLGA/Fibrin (PF), PLGA/Atelocollagen (PA). The constructs were cultured for three (3) weeks. They were evaluated based on gross morphological changes, cell proliferation (MTT) assay at 7, 14, 21 days of culture, and scanning electron microscopy (SEM) at the end of the 3-week culture. Histological stainings were used to evaluate the constructs’ ECM production level for three consecutive weeks. The outcome was further verified via sGAG assay. The present study’s findings indicated that the monolayer cultured chondrocytes could be transfected efficiently with the >10 kbp plasmid using the optimised lipofection procedure. The transfected chondrocytes produced ECM comparable to the control group. The resulting in vitro 3D “cell-scaffold” constructs exhibited a newly formed neocartilage tissue. The tissue can be further developed in vivo to complete tissue regeneration. The study showed that the SOX-trio and TERT genes transfer is beneficial for articular cartilage tissue engineering. The goal of TERM is to be of benefit to the patient by taking positive steps to prevent and remove harm from the patient. Hence, TERM advocates must strive to provide a proper standard of TERM use and care in clinical settings to avoid or minimise the risk of harm. This practice may be best supported by commonly held moral convictions and society’s laws.